Endogenous Expectations - Demski, Joel S. (The Accounting Review, 2004)
I selectively survey the use of expectations in accounting research. While expectations are central to modeling work and essential in empirical documentation, we tend to rely on largely exogenous expectations, as opposed to closing the analysis with aggressive identification of information sources and an explicit equilibrium argument.